2000
DOI: 10.1038/labinvest.3780039
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Caspase-3 in Hypertrophic Scars and Keloid: Induction of Caspase-3 and Apoptosis in Keloid Fibroblasts In Vitro

Abstract: SUMMARY:Recent studies have suggested that the regulation of apoptosis during wound healing is important in scar establishment and development of pathological scarring. To examine the phenomenon of apoptosis and its involvement in the process of pathological scarring, we immunohistochemically quantified differential levels of expression of caspase-3 and -2, which are activated during apoptosis in vitro, in surgical resected scar tissues. We divided 33 cases of normally healed flat scars and 18 cases of patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 49 publications
3
44
0
1
Order By: Relevance
“…However, the high level of the cytoprotective HSP 70 12 after 90 days indicates a permanent cell stress even at the interface of the LW mesh. Compared to investigations at scars 13,14 the measurements of the apoptosis and proliferation imply a considerably increased cell-turnover process in the HW group, whereas the LW mesh indicated almost physiological levels. In accordance with the present data, the persistently increased remodeling and cell turnover has been proved recently in human explanted heavyweight polypropylene mesh samples.…”
mentioning
confidence: 84%
“…However, the high level of the cytoprotective HSP 70 12 after 90 days indicates a permanent cell stress even at the interface of the LW mesh. Compared to investigations at scars 13,14 the measurements of the apoptosis and proliferation imply a considerably increased cell-turnover process in the HW group, whereas the LW mesh indicated almost physiological levels. In accordance with the present data, the persistently increased remodeling and cell turnover has been proved recently in human explanted heavyweight polypropylene mesh samples.…”
mentioning
confidence: 84%
“…Enhanced expression of activated caspase-3 in hypertrophied scars and keloid has been shown to induce apoptosis in fibroblasts. 23 Naturally occurring viral caspase inhibitors have the ability to inhibit caspase activation and activity, thus averting apoptotic cell death. Synthetic caspase inhibitors, such as ZVAD-fmk, applied directly to infarcting rat myocardium have been shown to limit infarct size.…”
Section: Caspase Inhibitionmentioning
confidence: 99%
“…Jiménez et al 38 indicated that c-myc and rho-p21 are potent inducers of apoptosis, whereas Bcl-2, v-abl, E1B, and ras prevent activation of the apoptotic pathway in fibroblasts. Akasaka et al 36 also reported that the increased expression of caspase-3 in keloids can induce apoptosis in fibroblasts. Since ROS production can induce apoptosis, we hypothesized that Nrf2 may be involved in this process.…”
Section: Discussionmentioning
confidence: 97%
“…Desmoulière et al 33 have shown that the number of apoptotic cells sharply increases as the wound closes, suggesting that apoptosis is involved in the progressive transformation of granulation tissue into scar. A few studies have reported increased apoptosis in keloid fibroblasts 5,36 . Akasaka et al 37 reported increased apoptosis in keloid fibroblast cells compared to normal fibroblasts and hypertrophic scars.…”
Section: Discussionmentioning
confidence: 99%